Reliability of panoramic radiography in assessing gonial angle compared to lateral cephalogram in adult patients with Class I malocclusion - Girish Katti; Chandrika Katti; Karuna; Syed Shahbaz; Munnawwarulla Khan; Sreenivas Rao Ghali (Journal of Indian Academy of Oral Medicine and Radiology, 2016)
Introduction: Gonial angle is an important angle of the craniofacial complex. Lateral cephalogram and orthopantomogram (OPG) can be used to determine this angle. Objectives: To investigate whether OPGs can be used as an alternative to lateral cephalogram for measuring the gonial angle. Study Design: A total of 100 radiographs were collected from patients with Angle's Class I malocclusion (50 males and 50 females) with age ranging from 15 to 30 years, with a mean age of 18.24 years. Materials and Methods: The radiographs were taken with digital panoramic system (Kodak 8000C) under standard exposure factors, as recommended by the manufacturer. Gonial angle was determined by the tangent of the inferior border of the mandible and the most distal aspect of the ascending ramus and condyle on both panoramic and cephalometric radiographs. Statistical Analysis: Mean values were evaluated using z test. The statistical analysis was performed by using the Statistical Package for the Social Sciences (version 11.5). Results: The mean gonial angle was 121.13° and 122.22° on panoramic and cephalometric radiographs, respectively. There was no statistical significant difference between the measured gonial angles on panoramic and cephalometric radiographs (P > 0.005). Conclusion: Panoramic radiography can be used to determine the gonial angle as accurately as lateral cephalogram. In addition, we can determine the right and left gonial angles of a patient in an OPG without interferences due to superimposed images of anatomical structures in lateral cephalogram.